Cover Picture: Biotechnology Journal 3/2019. Issue 3 (1st March 2019) - Unknown
Abstract : Biotechnology enable eco‐friendly factories based on the basic methodologies and automation technologies from full of natural resources, before long. For example, through the screenings from Actinomyces library, the novel producer of enzyme cocktail can be selected for efficiently degrading a plant biomass via various enzymes. These methods and findings are expected as the contribution of biobased economy in the future. This is reported by Musashi Takenaka, Jae M. Lee Prihardi Kahar, Chiaki Ogino, Akihiko Kondo in article1700744 .